Building personal resources through interventions: An integrative review. (15th May 2017) - Gilbert, Elisabeth; Foulk, Trevor; Bono, Joyce
Abstract: In recent years, a variety of disparate literatures have emerged to test interventions intended to increase individuals' psychological, cognitive, and physiological resources. Although many of these interventions were originally designed for individual or clinical use, a growing number of commentators have called for their adoption in organizations. But controversy remains about their efficacy in the workplace. We review the research literature on 6 interventions that have been used to build volatile personal resources: malleable, individual‐level constructs that are vital for withstanding work stress and proximal to work outcomes. In so doing, we evaluate the generalizability of these interventions to organizational settings, along with their potential benefits and costs. Our findings highlight new opportunities for both research and practice.